Vermiconversion of mixed leaves litter (pre-digested with fungal consortium) by using eudrilus eugeniae, perionyx excavatus and lampito mauritii (Funding work) - J. VIJI,; P.NEELANARAYANAN, (International Journal of Pharma and Bio Sciences, 2018)
The main objective of this research work is to utilize fungal consortium containing Aspergillus oryzae, Aspergillus fumigates and Rhizopus oryzae for the partial degradation of mixed leaves litter. The Vermicomposting ability of Eudrilus eugeniae, Perionyx excavatus and Lampito mauritii under monoculture (E I, E II and E III, respectively) and polyculture (E IV) conditions by using pre-digested mixed leaves litter in combination with cow dung (1:1 ratio) was studied. The conversion ratio of waste into vermicompost was in the order: E III > E IV> E I > E II. In the finished product the chemical nutrients and biological composition were measured. The vermicompost obtained from E III and E IV experimental trays were rich in macro and micro nutrients and microbial populations Therefore it may be concluded that the mixed leaves litter must be pre-digested with the chosen fungal consortium and be converted into vermicompost by using L. mauritii under Monoculture and E. eugeniae, P. excavatus and L. mauritii under Polyculture conditions.